Place-Based and People-Based Aspects of Street Sociability - Ujang, Norsidah; Rakhshanifar, Mahboubeh (Penerbit Akademia Baru, 2019)
The functions of streets as social places have been undermined by the emergence of modern shopping malls that focus on indoor social activities. Streets mainly use as channels for vehicular movement rather than spaces for social activities due to the dominance of car-oriented environment. In the context of Kuala Lumpur city, in spite of the high intensity of pedestrians in the main shopping streets fewer social activities observed especially in static form like sitting, standing and so forth. The lack of social activities in the main shopping streets could be due to the quality of the physical and the social environmental characteristics. The aim of this paper is to review the related theories explaining social logic of the streets. These theories include theory of change and behaviour setting, cities as movement economies, and third place theory. The finding of this paper would reveal the conceptual framework related to street sociability which would provide better understanding of the nature of the social activities and street sociability in the context of urban design.